Entomological Surveillance of the Invasive Aedes Species at Higher-Priority Entry Points in Northern Iran: Exploratory Report on a Field Study - Seyed Hassan Nikookar; Alireza Maleki; Mahmoud Fazeli-Dinan; Razieh Shabani Kordshouli; Ahmadali Enayati (JMIR Publications, 2022)
BackgroundArboviral diseases such as dengue, Zika, and chikungunya are transmitted by Aedes aegypti and Ae albopictus and are emerging global public health concerns. ObjectiveThis study aimed to provide up-to-date data on the occurrence of the invasive Aedes species in a given area as this is essential for planning and implementing timely control strategies. MethodsEntomological surveillance was planned and carried out monthly from May 2018 to December 2019 at higher-priority entry points in Guilan Province, Northern Iran, using ovitraps, larval collection, and human-baited traps. Species richness (R), Simpson (D), evenness (E), and Shannon-Wiener indexes (H̕) were measured to better understand the diversity of the Aedes species. The Spearman correlation coefficient and regression models were used for data analysis. ResultsWe collected a total of 3964 mosquito samples including 17.20% (682/3964) belonging to the Aedes species, from 3 genera and 13 species, and morphologically identified them from May 2018 to December 2019. Ae vexans and Ae geniculatus, which showed a peak in activity levels and population in October (226/564, 40.07% and 26/103, 25.2%), were the eudominant species (D=75.7%; D=21.2%) with constant (C=100) and frequent (C=66.7%) distributions, respectively. The population of Ae vexans had a significant positive correlation with precipitation (r=0.521; P=.009) and relative humidity (r=0.510; P=.01), whereas it was inversely associated with temperature (r=−0.432; P=.04). The Shannon-Wiener Index was up to 0.84 and 1.04 in the city of Rasht and in July, respectively. The rarefaction curve showed sufficiency in sampling efforts by reaching the asymptotic line at all spatial and temporal scales, except in Rasht and in October. ConclusionsAlthough no specimens of the Ae aegypti and Ae albopictus species were collected, this surveillance provides a better understanding of the native Aedes species in the northern regions of Iran. These data will assist the health system in future arbovirus research, and in the implementation of effective vector control and prevention strategies, should Ae aegypti and Ae albopictus be found in the province.